Reportaje audiovisual para visibilizar el freestyle en la ciudad de Machala - Muñoz Cabanilla, Washington Olmedo (Machala, 2019)
Audiovisual resources are one of the most effective ways to generate impact on the audience because they can contain a high degree of emotional load, this leads to reflection and questioning in those who receive and / or appreciate the audiovisual product. The report is considered one of the most complete journalistic genres, this is due to the investigative process that is carried out for its preparation, not only shows a fact, but also deepens giving a broader and more detailed view of the information. According to Vidal J. and Téllez A. the audiovisuals “allow subjective interpretation through the use of montage, shots and all kinds of resources that make it possible to capture reality from the reality lived, felt and perceived” (p565). Who performs the audiovisual work is involved in the process to understand and thus structure the plot line with which the story or event will be told to a certain audience. The sum of the story line, sequence of images, sound resources results in the effectiveness of an audiovisual product, in this case the report that accompanied by a journalistic investigation and adequate verification of sources of information will lead to the understanding of the public that will receive the product audiovisual. Freestyle is a practice inherent to urban culture, it is linked to the concept of appropriation of spaces within the environment that the individual develops, that is to say the city and this in turn goes hand in hand with the communicative process, since as mentioned Reguillo (1995) quoted from Cuesta O. and Meléndez S. (2017) “the city contains multiple identities, since it implies different relations with the territory, both real and symbolic, which results in social practices” (p208). The author emphasizes that there are 3 lines where communication intervenes in the city, territorial belonging and the exchange of meanings, the way in which the media intervene in the individual's daily relationship and the link of urban space with groups or movements social. The present investigation was oriented to the elaboration of a communicational product to make freestyle visible in the city of Machala, which arises from the need to give spaces to groups that do not have such a presence in the public imaginary, either due to the lack of dissemination of the media or ignorance of the population. After applying the methodological process, it was found that the Machalean citizens mostly ignore the background of freestyle and tend to associate it with concepts such as gangs and drugs. After a series of interviews with experts in communication and audiovisual producers it was determined that the ideal product to achieve the correct visibility of freestyle in Machala is through a report, which had the support and theoretical contrast of freestylers, experts in Psychology and Language and Literature. The product was disseminated through Facebook - YouTube and socialized in a focus group where the results obtained were favorable since they recognized that freestyle is a discipline that requires preparation and has nothing to do with the concepts mentioned above (drugs - gangs).
Los recursos audiovisuales son una de las formas de mayor efectividad para generar impacto en la audiencia debido a que pueden contener un alto grado de carga emocional, esto conlleva a la reflexión y cuestionamiento en quienes reciben y/o aprecian el producto audiovisual. El reportaje es considerado uno de los géneros periodísticos más completos, esto se debe al proceso investigativo que se lleva a cabo para su elaboración, no solo muestra un hecho, sino que se profundiza dando una visión más amplia y detallada de la información. Según Vidal J. y Téllez A. los audiovisuales “permiten la interpretación subjetiva a través del empleo del montaje, las tomas y todo tipo de recursos que posibilita captar la realidad desde la propia realidad vivida, sentida y percibida” (p565). Quien realiza el trabajo audiovisual se involucra dentro del proceso para entender y de esta forma estructurar la línea argumental con que contará la historia o suceso a una determinada audiencia. La suma del hilo argumental, secuencia de imágenes, recursos sonoros dan como resultado la efectividad de un producto audiovisual, en este caso el reportaje que acompañado de una investigación periodística y contraste adecuado de fuentes de información desembocaran en la comprensión del público que recibirá el producto audiovisual. El freestyle es una práctica inherente a la cultura urbana, está ligado al concepto de apropiación de espacios dentro del entorno que el individuo se desenvuelve, es decir la ciudad y esta a su vez va de la mano con el proceso comunicativo, ya que como menciona Reguillo (1995) citado de Cuesta O. y Meléndez S. (2017) “la ciudad encierra múltiples identidades, dado que implica diferentes relaciones con el territorio, tanto a nivel real como simbólico, lo que deriva en prácticas sociales” (p208). El autor hace énfasis en que existen 3 líneas donde la comunicación interviene en la ciudad, la pertenencia territorial y el intercambio de significados, la forma en como los medios intervienen en la relación cotidiana del individuo y el vínculo del espacio urbano con los grupos o movimientos sociales. La presente investigación se orientó a la elaboración de un producto comunicacional para visibilizar el freestyle en la ciudad de Machala, mismo que nace de la necesidad de dar espacios a grupos que no tienen tanta presencia en el imaginario público, ya sea por la falta de difusión de los medios o desconocimiento de la población. Tras aplicar el proceso metodológico se encontró que la ciudadanía machaleña en su mayoría desconoce el trasfondo del freestyle y tienden a asociarlo con conceptos como pandillas y drogas. Luego de una serie de entrevistas con expertos en comunicación y productores audiovisuales se determinó que el producto idóneo para lograr la correcta visibilización del freestyle en Machala es a través de un reportaje, mismo que contó con el sustentó y contraste teórico de freestylers, expertos en Psicología y Lengua y Literatura. El producto fue difundido a través de Facebook – YouTube y socializado en un focus group donde los resultados obtenidos fueron favorables ya que reconocieron que el freestyle es una disciplina que requiere de preparación y nada tiene que ver con los conceptos mencionados con anterioridad (drogas – pandillas).
Keywords: PRODUCCION AUDIOVISUAL; CULTURA URBANA; REPORTAJE; CIUDAD